Recovery of Copper (Cu) from printed circuit board (PCB) using LAKOS separator - Syed Aqil Syed Nadzir (Universiti Malaysia Perlis, 2008)
Printed Circuit Board (PCB) scrap has a metal content of nearly 28%, including an abundance of nonferrous metals such as copper, lead and tin. The purity of precious metals in PCBs is more than 10 times that of content-rich minerals. Therefore the recycling of PCBs is an important subject, not only from the viewpoint of waste treatment, but also with respect to the recovery of valuable materials. A study was carried out by using LAKOS Separator, to recover the Copper (Cu) contents which contain on motherboard PCBs. PCBs were collected in obsolete or defective personal computers which are the largest source of this kind of waste. The primary sample preparation method in this study was disassembly of electrical components such as ICs, transistors, etc followed by crushing, milling and sieving. In order to determine the composition of each element, Aqua Regia Solution was carried out for each size of sample; starting from 75 µm, 63 µm and < 63 µm. The separation process was carried out utilizing LAKOS Separator. Results show that size of sample < 63 µm and pressure of 3.00 kg/cm² is the most feasible for recovery process because in 30 minutes, 82% recovery of Cu can be obtained. It founds that LAKOS Separator is an efficient and environmental means for recovering metals from PCB as well as a potential method to be commercialized in industrial application.